The Clinical and Radiological Manifestations in Coronavirus Disease 2019 With Negative Nucleic Acid Results - Lang, Guanjing (Open Forum Infect Dis, 2020)
BACKGROUND: Coronavirus disease 2019 (COVID-19) was a new emerging disease with high infectiousness. Its diagnosis primarily depended on real-time polymerase chain reaction (RT-PCR) results. This study investigated epidemiological, clinical, and radiological characteristics of COVID-19 with negative RT-PCR results before confirmation. METHODS: Patients with COVID-19 were enrolled and divided into 2 groups: a negative group with negative RT-PCR results before confirmation and a positive group with positive results at the first detection. Epidemiological and clinical features were compared. Dynamic chest computerized tomography (CT) images of the negative group were evaluated. RESULTS: Ninety-nine laboratory-confirmed patients with COVID-19 including 8 patients (8%) with negative RT-PCR results were included. Patients from the negative group had similar epidemiological features: the average age (50.25 ± 13.27 years in the negative group and 53.70 ± 16.64 years in the positive group) and gender distribution (males made up 50% of the negative group and 62.6% of the positive group) were comparable. No significant differences were observed in clinical symptoms between the 2 groups. We found that fever was the most common symptom for both groups, followed by cough, expectoration, chest distress, fatigue, and gastroenterological symptoms. Moreover, ground-glass opacities and consolidations were the main manifestation in chest CT of patients with COVID-19 with or without confirmed RT-PCR results. CONCLUSIONS: Regardless of initial RT-PCR results, patients with COVID-19 had similar epidemiological, clinical, and chest CT features. Our study suggests value from early chest CT scans in COVID-19 screening and dynamic significance of radiology in disease monitoring should guide clinical decisions.